Grape Seed Proanthocyanidin Extract Moderated Retinal Pigment Epithelium Cellular Senescence Through NAMPT/SIRT1/NLRP3 Pathway - Zhu W (Dove Medical Press, 2021)
Wencui Wan,1,* Wei Zhu,2,* Yan Wu,3,4,* Yang Long,1 Hongzhuo Liu,1 Weiwei Wan,1 Guangming Wan,1 Jing Yu3 1Department of Ophthalmology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 2Department of Ophthalmology, Changshu No. 2 People’s Hospital, Changshu, People’s Republic of China; 3Department of Ophthalmology, Shanghai Tenth People’s Hospital, Tongji University, Shanghai, People’s Republic of China; 4Mois Biotech Company, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guangming WanDepartment of Ophthalmology, First Affiliated Hospital of Zhengzhou University, 1 East Jianshe Road, Zhengzhou, Henan, 450052, People’s Republic of ChinaEmail wgm6608@163.comJing Yu No. 301, Yanchang Road, Shanghai, 200072, People’s Republic of ChinaEmail dryujing@aliyun.comBackground: Retinal pigment epithelium (RPE) cellular senescence is an important process in degenerative retinal disorders. Grape seed proanthocyanidin extract (GSPE) alleviates senescence-related degenerative disorders; however, the potential effects of GSPE intake on RPE cellular senescence through regulating NAMPT/SIRT1/NLRP3 pathway remain unclear.Methods: The effects of GSPE on NAMPT expression and NAD+ contents were detected with Western blot and assay kit in both in-vivo and in-vitro AMD models. Senescence-related biomarkers, including p16, p21 expressions and β-gal staining, were conducted in different groups. The protective effects of GSPE treatment on the mitochondrial homeostasis and barrier function of RPE cells were detected using mtDNA lesions analyses, JC-1 staining, ZO1 staining and trans-epithelial cell resistance (TEER) detection. The expression of senescence-associated secretory phenotype (SASP) in different groups would be conducted with qPCR. To demonstrate the potential effects of NAMPT/SIRT1/NLRP3 pathway after GSPE treatment, the protein levels of relevant key regulators after applications of NAMPT inhibitor, Fk866, and SIRT1 inhibitor, EX-527.Results: GSPE significantly improves the NAMPT expression and NAD+ content in aging mice, and thus alleviates the RPE cellular senescence. In advanced in-vitro studies, GSPE significantly up-regulated NAMPT content and thus relieved H2O2 induced NAD+ depression through analyzing the NAD+ contents in different groups. In advanced analyses, it was reported that GSPE could alleviate mitochondrial permeability, mtDNA damage, ZO1 expression and SASP levels in aging RPE cells. Thus, GSPE treatment significantly decreased senescence-related protein p16 and p21, as well as SASP levels in in-vitro aging model, and it was demonstrated that GSPE could illustrate a significant anti-aging effect. The Western blot data in GSPE treatment of aging RPE cells demonstrated that GSPE could significantly improve NAMPT and SIRT1 levels, and thus depressed NLRP3 expression.Conclusion: This study indicated that GSPE alleviated RPE cellular senescence through NAMPT/SIRT1/NLRP3 pathway. This study highlighted the potential effects of GSPE on degenerative retinopathy through the crosstalk of NAD+ metabolism, SIRT1 function and NLRP3 activation.Keywords: cellular senescence, retinal pigment epithelium, nicotinamide phosphoribosyltransferase, sirtuin 1, inflammasome, NLRP3